Diy know-how with show-how - Cassell, Julian; Parham, P. [ (Peter)] , 1950- (DK, 2009)
In this manual step-by-step photographic sequences break down each stage of a job, from choosing tools to performing tasks to simple fixes for common problems. The overview feature keeps you on track by showing the entire sequence of events from start to finish.